О необходимости корректировки ряда нормативных правовых актов, определяющих содержание деятельности МЧС Республики Беларусь - Gur'ev, А. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The analysis of normative legal acts establishing functions and content of the Ministry for Emergency Situations activities as well of state system services of prevention and elimination of emergencies has been carried out. Taking into account attained experience, recommendations on further enhancement of the normative legal acts have been offered.